Anti-bird droppings photovoltaic panel self-cleaning coating and preparation method thereof

By preparing a specific combination of guano-resistant photovoltaic panel self-cleaning coating, using hydrophobic oleophobic properties and photocatalytic degradation function of nano-titanium dioxide, the reduction in power generation efficiency and material corrosion problems caused by bird guano pollution in mountain forest areas are solved, and the problem of photovoltaic equipment in mountainous and forest areas is realized. Long-term cleanliness of the panel and maintenance of power generation performance.

CN119286397AActive Publication Date: 2025-01-10ZHUHAI IRIDIUM NANOTECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411541508.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-10
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

Photovoltaic power generation equipment in mountain forest areas has reduced power generation efficiency and material corrosion due to bird guano pollution. The existing cleaning methods are costly and inefficient, so it is necessary to develop bird guano self-cleaning coatings to solve this problem.

Method used

It is made of octamethylcyclotetrasiloxane, tetramethyltri-3-trifluoropropylcyclotetrasiloxane, tetramethyldihydroxydisiloxane, heptadecafluorodecyltrimethoxysilane, and dioxide The self-cleaning coating of guano-resistant photovoltaic panels prepared by raw materials such as silicon aerogel, nanotitanium dioxide and tetramethylammonium hydroxide prevents guano from adhering to degrade pollutants through the hydrophobic oleophobic characteristics and the photocatalytic degradation function of nanotitanium dioxide.

Benefits of technology

The coating formed by the paint has excellent anti-dew on the adhesion and self-cleaning effect, which can effectively reduce the adhesion of the bird steak, reduce corrosion on the photovoltaic panel, keep the panel surface clean for a long time, extend the equipment life, and decompose under sunlight. Organic pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286397A_ABST
    Figure CN119286397A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an anti-bird droppings photovoltaic panel self-cleaning coating. The invention relates to a high-temperature-resistant coating, which is prepared from the following raw materials in a solvent through reaction: 45 to 60 parts of octamethylcyclotetrasiloxane, 90 to 120 parts of tetramethyltri-3-trifluoropropyl cyclotetrasiloxane, 10 to 12 parts of tetramethyldihydroxydisiloxane, 1 to 3 parts of heptadecafluorodecyl trimethoxysilane, 70 to 80 parts of octa (3-hydroxy-3-methylbutyl dimethyl siloxane), 2 to 5 parts of silicon dioxide aerogel and 18 to 20 parts of nano titanium dioxide. 1.5 to 3 parts of tetramethylammonium hydroxide and 45 to 60 parts of monohydroxyl-terminated polydimethylsiloxane. The coating has excellent bird droppings resistance, pollutants such as bird droppings and the like can be removed from the surface under the action of self gravity through wind blowing or rainfall washing, and the surface of the photovoltaic panel is kept clean for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new materials, and in particular relates to a self-cleaning coating for anti-guano photovoltaic panels and a preparation method thereof. Background Art

[0002] Photovoltaic power generation, as a new type of clean energy, has many advantages over traditional power generation, such as environmental protection, pollution-free, and noise-free. It is a sustainable new energy that my country has vigorously developed in recent years. With the increasingly widespread layout of photovoltaic projects, its application scenarios are no longer limited to plains and urban areas, but are expanding to more diversified geographical environments such as mountainous areas and sea areas. However, the development of photovoltaic power generation in mountainous and coastal areas has also brought new challenges. Especially in mountainous and coastal areas, due to the frequent activities of birds, pollutants such as bird droppings are very easy to adhere to the surface of photovoltaic panels, thus forming shielding. This shielding not only reduces the amount of sunlight received by photovoltaic panels, but also directly leads to a decrease in power generation efficiency. More seriously, the chemical components contained in bird droppings may corrode photovoltaic panels. Over a long period of time, these chemical components will gradually destroy the surface materials of photovoltaic panels, thereby affecting their overall performance and life. Considering the complexity and variability of the environment in mountainous and forested areas, the work of cleaning these pollutants is relatively difficult, and more manpower, material resources and time costs are required for regular cleaning and maintenance. Therefore, it is particularly important to develop a self-cleaning photovoltaic panel coating that can resist corrosion by acidic substances such as bird droppings. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide an anti-bird droppings photovoltaic panel self-cleaning coating and a preparation method thereof, which has an excellent effect of preventing bird droppings from adhering.

[0004] The technical solution adopted by the present invention is:

[0005] A self-cleaning paint for photovoltaic panels against bird droppings is obtained by reacting the following raw materials in a solvent: 45-60 parts of octamethylcyclotetrasiloxane, 90-120 parts of tetramethyltri-3-trifluoropropylcyclotetrasiloxane, 10-12 parts of tetramethyldihydroxydisiloxane, 1-3 parts of heptadecafluorodecyltrimethoxysilane, 70-80 parts of octa(3-hydroxy-3-methylbutyldimethylsiloxane), 2-5 parts of silicon dioxide aerogel, 18-20 parts of nano titanium dioxide, 1.5-3 parts of tetramethylammonium hydroxide and 45-60 parts of monohydroxy-terminated polydimethylsiloxane.

[0006] Preferably, the nano titanium dioxide is anatase nano titanium dioxide.

[0007] A method for preparing an anti-guano photovoltaic panel self-cleaning coating comprises the following steps:

[0008] (1) adding 45-60 parts of octamethylcyclotetrasiloxane, 90-120 parts of tetramethyltri-3-trifluoropropylcyclotetrasiloxane, and 10-12 parts of tetramethyldihydroxydisiloxane into a reactor, and continuously introducing an inert gas therein to expel air and moisture;

[0009] (2) adding 1.5 to 3 parts of tetramethylammonium hydroxide and stirring at 75-110° C. to complete the reaction;

[0010] (3) dissolving the obtained product in a volatile organic solvent, discarding the unreacted monomer in the lower layer after the solution is separated into layers, taking the upper layer solution, and performing a rotary evaporation operation under negative pressure to remove the solvent, thereby obtaining a fluorinated polysiloxane;

[0011] (4) Disperse 2-5 parts of silica aerogel and 18-20 parts of nano-titanium dioxide into anhydrous ethanol at a temperature T 1 Under stirring, 1 to 3 parts of heptadecafluorodecyltrimethoxysilane are slowly added until the reaction is complete to obtain a nanoparticle dispersion;

[0012] (5) adding the fluorinated polysiloxane obtained in step (3), 70 to 80 parts of octa(3-hydroxy-3-methylbutyldimethylsiloxane) and 45 to 60 parts of monohydroxy-terminated polydimethylsiloxane to the nanoparticle dispersion of step (4), and heating at a temperature T 2 Under stirring, the reaction is complete to obtain a self-cleaning coating for anti-guano photovoltaic panels.

[0013] The anti-guano photovoltaic panel self-cleaning coating and the curing agent hexamethylene diisocyanate trimer are stirred for 5 minutes until they are evenly stirred, and then the coating can be used as the coating to be sprayed; the curing agent can be any one of hexamethylene diisocyanate trimer, trimethyl hexamethylene diisocyanate, isophorone diisocyanate, tetramethylbenzylmethylene diisocyanate, and methylcyclohexyl isocyanate.

[0014] Preferably, the inert gas in step (1) is nitrogen.

[0015] Preferably, the volatile organic solvent in step (3) is ethanol.

[0016] Preferably, the evaporation operation in step (3) is rotary evaporation under negative pressure conditions.

[0017] Preferably, T 1 25~60℃, T 2 The temperature is 25-60° C. The purpose of heating is to accelerate the reaction rate.

[0018] The anti-bird droppings photovoltaic panel self-cleaning coating provided by the present invention has the following beneficial effects:

[0019] 1. The coating formed by the coating of the present invention has excellent hydrophobic and oleophobic effects. The coating is mainly composed of polysiloxane materials and introduces fluorine materials, which greatly improves the chemical composition of the surface and reduces the surface free energy, so that it can have excellent hydrophobic and oleophobic properties, repel various liquid pollutants, and prevent them from adhering to the surface of the photovoltaic panel;

[0020] 2. The coating formed by the coating of the present invention has an excellent effect of preventing bird droppings from adhering. The good chemical inertness of the fluorosilicone material can prevent various organic substances in the liquid bird droppings from forming an interaction force with the coating surface, weaken the adhesion of the bird droppings on the surface, and enable it to be removed from the surface by its own gravity by virtue of the excellent amphiphobicity of the coating; at the same time, the introduction of nano-titanium dioxide can decompose the organic pollutants on the surface under the irradiation of sunlight, and can achieve complete degradation for a small amount of bird droppings, and for a large amount of bird droppings, it can degrade the chemical bonds formed between the bird droppings and the coating surface, reduce the adhesion of the bird droppings, and enable it to be easily washed off the surface; nano-titanium dioxide can absorb part of the ultraviolet rays to prevent the coating from aging;

[0021] 3. The coating formed by the paint of the present invention has an excellent self-cleaning effect. When solid pollutants adhere to the surface of the photovoltaic panel, the low polarity composition of the coating surface can reduce the binding force between the solid pollutants and the coating surface, and can remove them from the surface under the action of its own gravity, wind or rainfall, thereby keeping the surface of the photovoltaic panel clean for a long time. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A comparison curve of transmittance in the visible light region between the photovoltaic panel glass coated with the anti-guano photovoltaic panel self-cleaning coating prepared in Example 1 of the present invention and the untreated photovoltaic panel glass.

[0023] Figure 2 A curve chart showing the anti-guano adhesion performance test of the anti-guano photovoltaic panel self-cleaning coating prepared in Example 1 of the present invention.

[0024] Figure 3 Degradation rate curve of the guano photodegradation performance test of the anti-guano photovoltaic panel self-cleaning coating prepared in Example 1 of the present invention.

[0025] Figure 4 Degradation cycle curve of the guano photodegradation performance test of the anti-guano photovoltaic panel self-cleaning coating prepared in Example 1 of the present invention.

[0026] Figure 5 Comparison curve of power generation efficiency of a photovoltaic panel coated with the anti-guano photovoltaic panel self-cleaning coating prepared in Example 1 of the present invention and an untreated photovoltaic panel before and after being placed in an outdoor environment for a long time. DETAILED DESCRIPTION

[0027] The specific implementation of the present invention is described in detail below in conjunction with specific implementation examples, but the present invention is not limited to the given examples.

[0028] Embodiment 1:

[0029] The specific preparation method of the anti-guano photovoltaic panel self-cleaning coating provided by the present invention is as follows:

[0030] (1) 50 g of octamethylcyclotetrasiloxane, 110 g of tetramethyltri-3-trifluoropropylcyclotetrasiloxane, and 12 g of tetramethyldihydroxydisiloxane were added to a reaction flask, and nitrogen was continuously introduced therein to expel air and moisture. Then 2 g of tetramethylammonium hydroxide was added, and the mixture was stirred and reacted at 80° C. for 6 hours. The obtained product was dissolved in ethanol and placed in a separatory funnel. The unreacted monomers in the lower layer were discarded, and the ethanol solution in the upper layer was taken and the ethanol was removed by rotary evaporation under negative pressure to obtain a fluorinated polysiloxane;

[0031] (2) 4 parts of silica aerogel and 19 g of nano-titanium dioxide were dispersed in 550 g of anhydrous ethanol, and ultrasonically dispersed for 15 minutes. 1 Stirring was continued at 60°C for 15 minutes, and then 2.5 g of heptadecafluorodecyltrimethoxysilane was added dropwise. After the addition was completed, the reaction was continued for 2 hours;

[0032] (3) Add the fluorinated polysiloxane prepared in step (1), 75 g of octa(3-hydroxy-3-methylbutyldimethylsiloxane) POSS and 55 g of monohydroxy-terminated polydimethylsiloxane to the nanoparticle dispersion of step (2) at T 2 The mixture was stirred at 60° C. for 1 hour to obtain a self-cleaning coating for anti-guano photovoltaic panels;

[0033] (4) Stir the anti-guano photovoltaic panel self-cleaning coating and 85 g of the curing agent hexamethylene diisocyanate trimer for 30 minutes until they are evenly stirred, and then the coating can be used as the coating to be sprayed;

[0034] (5) After the glass substrate used for the photovoltaic panel was rinsed twice with anhydrous ethanol and deionized water alternately, the coating was sprayed onto the surface of the photovoltaic glass panel, and the glass panel was kept horizontal during the spraying process. After curing for 2 hours at room temperature, an anti-bird droppings photovoltaic panel self-cleaning coating was prepared on the surface of the photovoltaic glass panel.

[0035] Example 2

[0036] The difference between this embodiment and embodiment 1 is that the added amounts of the components are 45 g of octamethylcyclotetrasiloxane, 10 g of tetramethyldihydroxydisiloxane, and 90 g of tetramethyltri-3-trifluoropropylcyclotetrasiloxane, and the heating temperature in step (1) is 75° C., T 1 At 25°C, T 2The temperature is 25°C, and the others are the same as in Example 1.

[0037] Example 3

[0038] The difference between this embodiment and embodiment 1 is that the added amounts of the components are 60 g of octamethylcyclotetrasiloxane, 12 g of tetramethyldihydroxydisiloxane, and 120 g of tetramethyltri-3-trifluoropropylcyclotetrasiloxane, and the heating temperature in step (1) is 110° C., T 1 At 40°C, T 2 The temperature is 40°C, and the others are the same as in Example 1.

[0039] Example 4

[0040] The difference between this embodiment and embodiment 1 is that the added amounts of the components are 18 g of nano titanium dioxide and 1.5 g of tetramethylammonium hydroxide, and the rest are the same as those in embodiment 1.

[0041] Example 5

[0042] The difference between this embodiment and embodiment 1 is that the added amounts of the components are 20 g of nano titanium dioxide and 3 g of tetramethylammonium hydroxide, and the rest are the same as those in embodiment 1.

[0043] Example 6

[0044] The difference between this embodiment and embodiment 1 is that the added amounts of components are 75 g of hexamethylene diisocyanate trimer and 45 g of monohydroxyl-terminated polydimethylsiloxane. The other contents are the same as those in embodiment 1.

[0045] Example 7

[0046] The difference between this embodiment and embodiment 1 is that the added amounts of components are 100 g of hexamethylene diisocyanate trimer and 60 g of monohydroxyl-terminated polydimethylsiloxane. The other contents are the same as those in embodiment 1.

[0047] Example 8

[0048] The difference between this embodiment and embodiment 1 is that the added amounts of components are 1 g of heptadecafluorodecyltrimethoxysilane, 70 g of octa(3-hydroxy-3-methylbutyldimethylsiloxane), and 2 g of silica aerogel. The rest are the same as embodiment 1.

[0049] Example 9

[0050] The difference between this embodiment and embodiment 1 is that the added amounts of components are 3 g of heptadecafluorodecyltrimethoxysilane, 80 g of octa(3-hydroxy-3-methylbutyldimethylsiloxane), and 4 g of silica aerogel. The rest are the same as embodiment 1.

[0051] The coating prepared in the embodiment of the present invention was tested for performance as follows:

[0052] Visible light transmittance measurement: The transmittance of the samples (coated glass and untreated glass) to visible light was tested using an Agilent Cary 5000 UV-visible-near infrared spectrophotometer. The size of the test sample was 7.5 cm × 2.5 cm, and a glass slide of the same size was selected as a control sample during the test. The transmittance of air was set as the baseline for the test. The test wavelength range was 300 nm to 800 nm.

[0053] Contact angle measurement: The contact angle of water droplets / oil droplets (if not otherwise specified, the oils used in the test here are all gasoline, i.e., a mixture of aliphatic hydrocarbons and cycloalkanes) on the coating surface was measured using the KRüSSDSA25S optical contact angle analysis system. For the measurement of the contact angle in a non-moving state, a water droplet / oil droplet (about 10 microliters) was first added to the sample surface by a motor-controlled syringe. When the droplet is stable, a side image is taken with a camera, and the software is used for fitting calculation to obtain the static contact angle value of the water droplet / oil droplet on the coating surface.

[0054] Sliding angle measurement: The sliding angle of water / oil droplets on the coating surface was measured using the KRüSSDSA25S optical contact angle analysis system. For sliding angle measurement, a motor-controlled rotatable test platform is used to tilt the sample, and the rotation angle of the platform is displayed in real time on a computer connected to the motor. At the beginning of the test, the initial inclination angle of the platform is maintained at 0°. After a water / oil droplet (approximately 10 microliters) is added to the coating surface through a syringe, the motor is controlled to rotate the platform. The rotation stops at the moment the droplet begins to slide on the surface, and the rotation angle displayed on the computer is recorded as the rolling angle. Each sample is measured at three different positions to reduce data errors.

[0055] Anti-bird droppings adhesion test: The anti-bird droppings deposition and adhesion test was conducted using an aqueous solution of pancreatic enzymes to simulate bird droppings. During the test, the coated glass substrate and the untreated glass substrate were placed in a forced air drying oven at an inclination angle of 20°, and then 3 g of an aqueous solution of pancreatic enzymes (10 wt% pancreatic enzymes) was added dropwise to the sample surface. After the temperature was raised to 60°C and the sample was allowed to stand for three hours, the mass of the attached material on the sample surface was weighed and recorded as the mass of the bird droppings attached to the sample surface. The surface was then rinsed with water, and the mass of the residue on the sample surface was weighed again after the water was dried.

[0056] Guano photodegradation performance test: The guano photodegradation curve of the coating surface is simulated by pancreatic enzyme aqueous solution. During the test, the glass substrate sprayed with the coating is placed horizontally, and then 1g of pancreatic enzyme aqueous solution (10wt% pancreatic enzyme) is dripped onto the sample surface. After the temperature is raised to 60℃ and the sample is left to stand for three hours to dry the water, the sample is placed under a 365nm light source, and the sample weight is weighed at intervals to calculate the degradation rate. The degradation cycle test repeats the above operation many times and calculates the degradation rate each time to measure the long-term durability of the coating against the guano photodegradation performance. If the degradation rate drops by more than 15 percentage points compared to the initial degradation rate, it is considered a failure, the test is stopped, and the number of test cycles is recorded.

[0057]

[0058] Coating adhesion test: The adhesion of the coating was tested according to ASTM D3359. All test samples were cross-cut at 1 mm intervals with a QHF grid cutter, and then 3MTM 600 tape was firmly pasted on the grid area, and then a 2 kg weight was placed on the tape pasting area and slid and pressed to make the tape fully contact the test area. After 90 seconds of rest, the tape was quickly pulled apart in the vertical direction (90°), and the same area was tested twice, and then the remaining part of the coating on the substrate was observed to evaluate the adhesion of the coating. According to the standard, when the coating falls off about 0%, its adhesion is 5B grade; when the coating falls off less than 5%, the adhesion is 4B grade; when the coating falls off less than 15%, the adhesion is 3B grade; when the coating falls off less than 35%, the adhesion is 2B grade; when the coating falls off less than 65%, the adhesion is 1B grade; when the coating falls off more than 65%, the adhesion is 0B grade.

[0059] Coating wear resistance test: Taber wear tester was used to test the coating wear resistance according to ASTM standard test (D4060 standard). During the test, a 250g load grinding wheel ( Industries Cs-10) is used as the wear medium. First, the coating is sprayed onto a specific annular glass substrate, and then fixed to the sample stage of the Taber wear tester. A wear wheel is lowered on each side to closely adhere to the surface of the test sample. When the test starts, the sample stage will rotate with the tested sample. Here, one rotation of the sample is defined as a test cycle. After the test, the wear resistance is measured by calculating the weight loss rate of the sample and the changes in transmittance and anti-wetting properties.

[0060] The calculation formula of weight loss rate is as follows:

[0061]

[0062] Coating anti-UV test: The coating's anti-UV performance is tested under a UV lamp with a wavelength of 365 nanometers and a power of 300 watts. After the sample is irradiated for a specified time, the changes in the sample's transmittance and anti-wetting properties are tested to measure the UV resistance.

[0063] Coating weather resistance test: The weather resistance of the coating is tested in a constant temperature and humidity chamber. The constant temperature and humidity chamber is set at 50°C and 95% humidity to simulate a high temperature and high humidity environment. After the sample is placed for a specified time, the changes in the transmittance and anti-wetting properties of the sample are tested to measure the weather resistance.

[0064] Comparative test of photovoltaic cell power generation efficiency: During the power generation efficiency test, commercial unpackaged photovoltaic silicon wafers were selected as test photovoltaic cells, and the surface was covered with a glass substrate sprayed with a coating and an untreated glass substrate to compare the effect of the test coating on the power generation efficiency of the battery module. The current density-voltage curve was tested by the Taitaishi PROVA200A solar cell analyzer. The solar light source during the test was provided by the Yiguangke SOLARBEAM-06-3A sunlight simulator, simulating AM 1.5 sunlight of about 100mW·cm -2 The radiation intensity.

[0065] The above test method was used to test the performance of the coatings formed by coating the photovoltaic glass panels with the coatings prepared in each embodiment. The results are shown in the following table:

[0066]

[0067]

[0068] It can be seen from the above table that the contact angle of water droplets on the coating surface is greater than 112°, indicating that the coating has excellent hydrophobic properties. Water droplets cannot spread on the surface and can easily slide off the surface at an inclination angle of less than 20°, effectively preventing the formation of water stains on the surface and reducing the loss of transmittance caused by water accumulation on the surface during use; similarly, the contact angle of oil droplets on the coating surface is greater than 78°, up to 91.39°, and the minimum sliding angle is only 3.31°, indicating that the coating has excellent oleophobic properties, which can greatly avoid the adhesion of oil pollutants on the surface, keep the surface of the photovoltaic panel clean, and maintain a high level of power generation.

[0069] According to the above table data and Figure 1From the comparison curve of the transmittance in the visible light region between the photovoltaic panel glass coated with the coating of the present invention and the untreated photovoltaic panel glass, it can be seen that within the wavelength range of 400-800 nanometers, the transmittance of the coated glass and the untreated glass is not much different, both at the level of about 92%±0.5%. The coating of the present invention will not affect the transmittance of light, and can ensure that the photovoltaic panel maintains a high level of power generation.

[0070] from Figure 2 From the bar graph of the test results of the anti-guano adhesion performance of the self-cleaning coating for anti-guano photovoltaic panels, it can be seen that after drying, the surface of the glass substrate coated with the coating has about 0.064g of pancreatic enzyme solution residue adhered to the surface, while the surface of the untreated glass substrate has about 0.286g of pancreatic enzyme solution residue adhered to the surface. Almost all of the pancreatic enzyme solution remains on the surface of the untreated glass substrate. In comparison, the anti-guano photovoltaic panel self-cleaning coating has excellent anti-guano adhesion performance; after rinsing with water, the mass of the attached material on the surface of the glass substrate coated with the coating dropped to 0.021g, which is almost negligible, while the mass of the attached material on the surface of the untreated glass substrate is still as high as 0.249g, indicating that even if there is a small amount of bird droppings attached to the surface of the self-cleaning coating of the anti-guano photovoltaic panel, it can be easily removed from the surface by washing with external water flow, reducing the corrosion of the glass material by substances in the bird droppings and causing irreversible damage to the photovoltaic module.

[0071] from Figure 3 From the degradation rate curve in the guano photodegradation performance test of the photovoltaic panel glass surface coated with the anti-guano photovoltaic panel self-cleaning coating, it can be seen that with the increase of illumination time, the degradation rate of the guano simulant gradually increases, indicating that the mass of the guano simulant on the coating surface gradually decreases under the action of titanium dioxide photocatalytic decomposition. It can be seen that the titanium dioxide filler introduced into the coating is able to photodegrade organic pollutants on the surface under the condition of light irradiation.

[0072] from Figure 4 As can be seen from the degradation cycle test curve, in the 50-cycle test of bird droppings simulant placement-darkness-light degradation-placement on the photovoltaic panel glass surface coated with the same anti-guano photovoltaic panel self-cleaning coating, it can be seen that its degradation efficiency is always maintained at a high level, indicating that the photodegradation durability of the coating is very good and can meet the long-term service requirements of the coating on the photovoltaic panel surface.

[0073] from Figure 5The comparison curve of the power generation efficiency of the photovoltaic panel coated with the anti-guano photovoltaic panel self-cleaning coating and the untreated photovoltaic panel before and after being placed in an outdoor environment for a long time shows that at the beginning of the test, the open circuit voltage and short circuit current of the two are almost equal, which shows that the coating will not have too much impact on the original performance of the photovoltaic panel and can maintain the original power generation efficiency of the photovoltaic panel. After 60 days of outdoor placement, the power generation efficiency of the untreated photovoltaic panel has dropped significantly. This is mainly because the accumulation of pollutants on the surface of the photovoltaic panel affects the light intake and reduces the power generation level of the photovoltaic panel; while the photovoltaic panel coated with the anti-guano photovoltaic panel self-cleaning coating has only slightly decreased in power generation efficiency even after 60 days. It shows that the coating of the present invention has excellent anti-guano adhesion and self-cleaning properties, can keep the surface of the photovoltaic panel clean in an outdoor environment, and maintain a high level of power generation.

[0074] The present invention has been described in detail above in conjunction with specific embodiments. However, the present invention is not limited to the above description. Various changes made within the knowledge of those skilled in the art without departing from the concept of the present invention still fall within the protection scope of the present invention.

Claims

1. A self-cleaning coating for photovoltaic panels against bird droppings, characterized in that: The invention is obtained by reacting raw materials including the following components in a solvent: 45-60 parts of octamethylcyclotetrasiloxane, 90-120 parts of tetramethyltri-3-trifluoropropylcyclotetrasiloxane, 10-12 parts of tetramethyldihydroxydisiloxane, 1-3 parts of heptadecafluorodecyltrimethoxysilane, 70-80 parts of octa(3-hydroxy-3-methylbutyldimethylsiloxane), 2-5 parts of silicon dioxide aerogel, 18-20 parts of nano titanium dioxide, 1.5-3 parts of tetramethylammonium hydroxide and 45-60 parts of monohydroxy-terminated polydimethylsiloxane.

2. The anti-guano photovoltaic panel self-cleaning coating according to claim 1, characterized in that: The nano titanium dioxide is anatase nano titanium dioxide.

3. A method for preparing a self-cleaning coating for anti-guano photovoltaic panels, comprising the following steps: (1) adding 45-60 parts of octamethylcyclotetrasiloxane, 90-120 parts of tetramethyltri-3-trifluoropropylcyclotetrasiloxane, and 10-12 parts of tetramethyldihydroxydisiloxane into a reactor, and continuously introducing an inert gas therein to expel air and moisture; (2) adding 1.5 to 3 parts of tetramethylammonium hydroxide and stirring at 75-110° C. to complete the reaction; (3) dissolving the obtained product in a volatile organic solvent, separating the solution into layers, discarding the unreacted monomer in the lower layer, taking the upper layer solution, and removing the solvent by evaporation to obtain a fluorinated polysiloxane; (4) dispersing 2-5 parts of silica aerogel and 18-20 parts of nano-titanium dioxide in anhydrous ethanol, stirring at a temperature T1, and slowly adding 1-3 parts of heptadecafluorodecyltrimethoxysilane until the reaction is complete to obtain a nanoparticle dispersion; (5) Add the fluorinated polysiloxane obtained in step (3), 70 to 80 parts of octa(3-hydroxy-3-methylbutyldimethylsiloxane) and 45 to 60 parts of monohydroxy-terminated polydimethylsiloxane to the nanoparticle dispersion of step (4), stir at temperature T2, and react completely to obtain an anti-guano photovoltaic panel self-cleaning coating.

4. The method for preparing a self-cleaning coating for anti-guano photovoltaic panels according to claim 3, characterized in that: The inert gas in step (1) is nitrogen.

5. The method for preparing a self-cleaning coating for anti-guano photovoltaic panels according to claim 3, characterized in that: The volatile organic solvent in step (3) is ethanol.

6. The method for preparing a self-cleaning coating for anti-guano photovoltaic panels according to claim 3, characterized in that: The evaporation operation in step (3) is rotary evaporation under negative pressure conditions.

7. The method for preparing a self-cleaning coating for anti-guano photovoltaic panels according to claim 3, characterized in that: T1 is 25~60℃.

8. The method for preparing a self-cleaning coating for anti-guano photovoltaic panels according to claim 3, characterized in that: T2 is 25~60℃.

Citation Information

Patent Citations

  • Self-cleaning wear-resistant waterborne polyurethane exterior wall coating and preparation method thereof

    CN112694829A

  • Solar photovoltaic panel surface self-cleaning coating and preparation method thereof

    CN114231177A

  • Long-acting ceramic non-stick coating containing active fluorine-silicon multifunctional additive and preparation method of long-acting ceramic non-stick coating

    CN116042087A

  • High-wear-resistance water-based elastic coating

    CN118406427A